Analysis of Watersheds in Gandaki Province, Nepal Using QGIS (Technical Journal, 2019)
Gandaki province has the good potentiality of hydro-electricity generation with existing twenty-nine hydro-electricity projects. Since the Province is rich in water resources, analysis of watersheds needs to be done for management, planning and identification of water as well as natural resources. GIS offers integration of spatial and no spatial data to understand and analyze the watershed processes and helps in drawing a plan for integrated watershed development and management. The Digital Elevation Model (DEM) available on the NASA-Earth data has been taken as a primary data for morphometric analysis of watershed in Gandaki Province using QGIS. Delineation of watershed was conducted from a DEM by computing the flow direction and using it in the Watershed tool. Necessary fill sink correction was made before proceeding to delineation. A raster representing the direction of flow was created using Flow Direction tool to determine contributing area. Flow accumulation raster was created from flow direction raster using Flow Accumulation Tool. A point-based method has been used to delineate watershed for each selected point. The selected point may be an outlet, a gauge station or a dam. The annual rainfall data from ground meteorological stations has been used in QGIS to generate rainfall map for the study of rainfall pattern in the province and watersheds using IDW Interpolation method. The present research work provides some major morphometric watershed parameters like drainage area, flow length, slope, drainage density and rainfall patterns for watersheds in Gandaki Province. Furthermore, the parameters were compared among the watersheds in Kaski. The results of this study can be used as a reference for proposing infrastructures in those watersheds and it can also be used for making policy by local government authorities related to Energy, Water Resources, Irrigation, and Infrastructures.